2015
DOI: 10.2147/ccid.s67826
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of a topical mixture with ozolipoile in the treatment of actinic ulcers

Abstract: PurposePost-radiation skin damage is the result of alterations produced in the irradiated zone. There are different studies aimed at verifying the effectiveness of several kinds of molecules in the treatment of radiation-induced skin damage. The purpose of this study is to test a mixture with a formulation containing several natural active ingredients on actinic ulcers in patients receiving radiation therapies.Patients and methodsThe authors recruited 13 patients, and randomly divided them into a test group (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Among all the included 12 articles with 1055 participants, the publishing dates ranged from 2005 to 2020. Involved wound types include second‐ or third‐degree actinic ulcers following a radiotherapy cycle, 25 chronic venous leg ulcers, 28,33 digital ulcers (DUs) in systemic sclerosis (SSc), 32 critical limb ischemia (CLI), 24 and diabetic foot ulcers 11,15,26,27,29‐31 . The proportion of participants with completely healed wounds were reported in seven trials 11,15,26,28,29,32,33 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among all the included 12 articles with 1055 participants, the publishing dates ranged from 2005 to 2020. Involved wound types include second‐ or third‐degree actinic ulcers following a radiotherapy cycle, 25 chronic venous leg ulcers, 28,33 digital ulcers (DUs) in systemic sclerosis (SSc), 32 critical limb ischemia (CLI), 24 and diabetic foot ulcers 11,15,26,27,29‐31 . The proportion of participants with completely healed wounds were reported in seven trials 11,15,26,28,29,32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve RCTs contributed to this systematic review. 11 , 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 A diagram of the selection of studies is shown in Figure 1 . A list of records excluded by reading the full text is shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excellent results have been obtained on soft tissues, even from the use of a mixture of ozolipoilein, which, in only 3–5 days, can heal small ulcers caused by radiation therapy cycles. This blend is also antibacterial and antifungal [ 181 ]. Instead, PRF significantly contributes to tissue healing through its antibacterial properties, especially against S. aureus and E. Coli.…”
Section: Platelet Derivates and Growth Factorsmentioning
confidence: 99%